2014
DOI: 10.1021/ja413036q
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme-Responsive Amphiphilic PEG-Dendron Hybrids and Their Assembly into Smart Micellar Nanocarriers

Abstract: Enzyme-responsive micelles have great potential as drug delivery platforms due to the high selectivity of the activating enzymes. Here we report a highly modular design for the efficient and simple synthesis of amphiphilic block copolymers based on a linear hydrophilic polyethyleneglycol (PEG) and an enzyme-responsive hydrophobic dendron. These amphiphilic hybrids self-assemble in water into micellar nanocontainers that can disassemble and release encapsulated molecular cargo upon enzymatic activation. The uti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
170
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(180 citation statements)
references
References 23 publications
7
170
1
Order By: Relevance
“…Biological stimulus, such as enzyme, represents an attractive alternative in the synthetic assemblies that have been recognized as promising class of drug delivery systems [15,16].…”
Section: (C) Effect Of Enzyme On Azo-ag 5 Nanostructuresmentioning
confidence: 99%
See 2 more Smart Citations
“…Biological stimulus, such as enzyme, represents an attractive alternative in the synthetic assemblies that have been recognized as promising class of drug delivery systems [15,16].…”
Section: (C) Effect Of Enzyme On Azo-ag 5 Nanostructuresmentioning
confidence: 99%
“…Applying external stimuli such as light [10,11], heat [12], pH [5,6,13] and also biological stimuli such as enzyme [14][15][16], assembly and disassembly of these systems can be regulated. Recently, light irradiation, which is quite energy-saving and easily controllable, is considered as the most reliable external stimulus [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14,15 Studies demonstrated that designed functional polymeric micelles were able to stably encapsulate drugs and release them at tumor sites in response to external stimuli such as redox, pH, temperature, and enzyme conditions. [16][17][18][19] In particular, redox-sensitive micelles were designed to trigger burst drug release owing to the high concentration of glutathione (GSH, 4 μΜ/g) that is normally found in tumor tissues. 20,21 Disulfide bond is stable under normal physiological conditions yet responsive to the reductive environment (eg, GSH) of intracellular fluids in cancer cells, indicating that disulfide bonds can be used as the linker of hydrophilic and hydrophobic portions in the redox-sensitive polymeric micelles for controlling the delivery of intracellular drug.…”
Section: Introductionmentioning
confidence: 99%
“…Stimuli-responsive DDCs can release encapsulated anticancer drug upon environmental stimuli, which is playing an increasingly crucial role in the disease treatment [21]. These environmental stimuli involve pH [22], redox reactions [23], enzymatic expression [24], temperature [25], irradiated light [26], magnetic field [27], or their combination. Among the various redox sensitive DDCs, disulfide bond is of great interest because of its instability under the reduced glutathione (GSH).…”
Section: Introductionmentioning
confidence: 99%